Recurring Styles #9 - Integers for a Condition!

( n + 1 ) ( n 2 ) x n + 1 = n ( n 2 n 1 ) x n ( n 1 ) 3 x n 1 \large{(n+1)(n-2)x_{n+1} = n(n^2 - n - 1)x_n - (n-1)^3 x_{n-1}}

Let ( x n ) n 2 (x_n)_{n \geq 2} be a sequence such that x 2 = 1 , x 3 = 1 x_2 = 1, x_3 = 1 , and for all n 3 n \geq 3 , the above recurrence relation satisfies.

For which all values of n , n 4 n, \ n \geq 4 is every x n x_n an integer?

Only when n n is an odd number. Only when n n is an even number. Only when n n is a prime number. Only when n 1 ( m o d 4 ) n \equiv 1 \pmod 4 . Only when n 1 ( m o d 6 ) n \equiv 1 \pmod 6 . Only when n 1 ( m o d 4 ) n \equiv -1 \pmod 4 . Only when n 1 ( m o d 6 ) n \equiv -1 \pmod 6 .

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Satyajit Mohanty
Aug 23, 2015

Let y n = n x n 1 y_n = nx_n - 1 . Then y 2 = 1 , y 3 = 2 y_2 = 1, y_3 = 2 and for n 3 n \geq 3 ,

( n 2 ) y n + 1 = ( n 2 n 1 ) y n ( n 1 ) 2 y n 1 \large{(n-2)y_{n+1} = (n^2 - n - 1)y_n - (n-1)^2 y_{n-1}}

thus, ( n 2 ) ( y n + 1 y n ) = ( n 1 ) 2 ( y n y n 1 ) (n-2)(y_{n+1} - y_n) = (n-1)^2 (y_n - y_{n-1})

Let z n = y n y n 1 z_n = y_n - y_{n-1} . Then z 3 = 1 z_3 = 1 and z n + 1 = ( n 1 ) 2 n 2 z n z_{n+1} = \dfrac{(n-1)^2}{n-2} z_n for n 3 n \geq 3 .

It follows easily that z n = ( n 2 ) ( n 2 ) ! z_n = (n-2) \cdot (n-2)! for all n 3 n \geq 3 . Then:

y n = ( y n y n 1 ) + ( y n 1 y n 2 ) + ( y n 2 y n 3 ) + + ( y 3 y 2 ) + y 2 \large{y_n = (y_n - y_{n-1}) + (y_{n-1} - y_{n-2}) + (y_{n-2} - y_{n-3}) + \ldots + (y_3 - y_2) + y_2 }

= z n + z n 1 + z n 2 + + z 3 + y 2 = 1 + k = 1 n 2 k k ! = ( n 1 ) ! \large{= z_n + z_{n-1} + z_{n-2} + \ldots + z_3 + y_2 = 1 + \sum_{k=1}^{n-2} k \cdot k! = (n-1)! }

And the last equality can be obtained by Induction or telescoping series, etc.

Therefore for n 2 n \geq 2 , we have x n = ( n 1 ) ! + 1 n x_n = \dfrac{(n-1)! +1}{n} .

Thus, x n x_n is an integer if and only if n n divides ( n 1 ) ! + 1 (n-1)! +1 , which is equivalent to n n being prime, according to Wilson's Theorem .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...